2018
DOI: 10.3390/rs10122046
|View full text |Cite
|
Sign up to set email alerts
|

The Spatio-Temporal Evolution of River Island Based on Landsat Satellite Imagery, Hydrodynamic Numerical Simulation and Observed Data

Abstract: A river island is a shaped sediment accumulation body with its top above the water’s surface in crooked or branching streams. In this paper, four river islands in Yangzhong City in the lower reaches of the Yangtze River were studied. The spatio-temporal evolution information of the islands was quantitatively extracted using the threshold value method, binarization model, and cluster analysis, based on Thematic Mapper (TM) and Enhanced Thematic Mapper+ (ETM+) images of the Landsat satellite series from 1985 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Fish mouths impede the flow of streamflow to some extent [26][27][28][29], and there are significant differences in the hydrodynamic elements of the inner and outer rivers of the canal. This is due to the fact that the fish mouth causes the outer riverbed of the canal to sink, while the inner river rises.…”
Section: Discussionmentioning
confidence: 99%
“…Fish mouths impede the flow of streamflow to some extent [26][27][28][29], and there are significant differences in the hydrodynamic elements of the inner and outer rivers of the canal. This is due to the fact that the fish mouth causes the outer riverbed of the canal to sink, while the inner river rises.…”
Section: Discussionmentioning
confidence: 99%
“…Hudson et al (2019) reported that sedimentary deposition directly prompted the formation of fluvial islands. Shi et al (2018) showed that the key natural factor that influences island formation in the lower Yangtze River was sediment discharge. In addition, Gao C. et al (2013) stated that there were no significant relationships between changes in the island area and natural factors, such as annual runoff and precipitation, and speculated that the construction of many large reservoirs could be the primary factor of change.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars investigated the evolution processes of MCBs based on the data of river topography or remote sensing images (Lou et al, 2018; Smith & Winkley, 1996; Wang & Xu, 2018; Wang, Dai, et al, 2018; Wang, Li, & Cai, 2018). These studies at the early stage mainly focused on the investigation of causes and required conditions for the MCB formation (Ashworth et al, 2000; Słowik, 2018) or the numerical simulation methods for the adjustment processes of sandbars (Luchi et al, 2010; Nicholas et al, 2013; Repetto et al, 2002; Shi et al, 2018). Then increasing attention was progressively paid to study the evolution characteristics of MCBs downstream of a dam.…”
Section: Introductionmentioning
confidence: 99%